2021
DOI: 10.2196/27626
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the National Tuberculosis Surveillance System in Sana’a, Yemen, 2018: Observational Study

Abstract: Background Tuberculosis remains a public problem that is considered one of the top causes of morbidity and mortality worldwide. The National Tuberculosis Control Program in Yemen was established in 1970 and included in the national health policy under the leadership of the Ministry of Public Health and Population to monitor tuberculosis control. The surveillance system must be evaluated periodically to produce recommendations for improving performance and usefulness. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
(25 reference statements)
1
4
0
Order By: Relevance
“…The TB Surveillance System faces notable gaps and issues regarding data quality and analysis. This finding is consistent with the findings of other studies 33 , 34 but inconsistent with the findings of other studies. 35 , 36 Without meaningful data to inform public health action, Jordan is likely to fall short of its goal of eliminating TB.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The TB Surveillance System faces notable gaps and issues regarding data quality and analysis. This finding is consistent with the findings of other studies 33 , 34 but inconsistent with the findings of other studies. 35 , 36 Without meaningful data to inform public health action, Jordan is likely to fall short of its goal of eliminating TB.…”
Section: Discussionsupporting
confidence: 72%
“…In other countries, some studies reported poor ratings of the simplicity of the system for several reasons including data collection is time-consuming and report forms are not easy to fill. 3 , 34 , 37 However, other studies in Yemen, Pakistan, and South Africa 35 , 39 , 40 reported that the system is simple. On the other hand, flexibility was rated good with some updates that need to be reflected in the dataset.…”
Section: Discussionmentioning
confidence: 96%
“…TB remains a major public health problem in developing countries such as Yemen, where NTP is the main health entity that deals with active TB cases. Before the outbreak of the civil war, the NTP budget was provided by international donors to the ministry of public health and population to cover NTP activities across the country [4]. However, as of 2015, the International Organization for Migration (IOM) has become the intermediary between international donors and the NTP in Yemen.…”
Section: Discussionmentioning
confidence: 99%
“…According to the WHO estimates, 14,700 TB patients were reported in Yemen in 2020, with an incidence rate of 49/100,000 people and a mortality rate of 7.3.100,000 people [3]. It should be noted that the only source of data on the number of TB cases in the country is the National TB Program (NTP), which was established in 1970 [4]. Due to the civil war, Yemen currently suffers from poverty and social unrest, which are factors that seriously affect TB infection rates.…”
mentioning
confidence: 99%
“…In 1970, the National Tuberculosis Control Program (NTCP) was established in Yemen to implement strategies and policies related to the control, treatment, and prevention of tuberculosis, including the World Health Organization (WHO) End Tuberculosis Strategy. In addition, the NTCP has adopted the directly observed therapy (DOT) Strategy since 1995 and expanded it gradually until full coverage in all the TB units in Yemen was realized [ 7 ].…”
Section: Introductionmentioning
confidence: 99%